Fungal cellulases: Production by solid-state cultivation in packed-bed bioreactor using solid agro-industrial by-products as substrates and application for hydrolysis of sugarcane bagasse - Casciatori Frassatto, Priscila Aparecida [UNESP] (2020)
Cellulases are essential for the hydrolysis of lignocellulosic materials in the production of second generation ethanol. Solid-state cultivation is a process that provides high concentrations of enzymes that can be used in this hydrolysis. The objectives of this work were to produce cellulases by cultivating the fungus Myceliophthora thermophila I-1D3b in a packed bed bioreactor with sugarcane bagasse (SCB) and wheat bran (WB) as substrate and to evaluate the efficiency of the enzymatic extract in the hydrolysis of SCB in natura (BIN) and pretreated with ozone, alkali and ultrasound (BOU). The conditions for enzyme production in the bioreactor were SCB:WB at a ratio of 2.3:1 (w/w), 75 % moisture content; 45 ºC; aeration rate 240 L h-1 and 96 h. The enzyme production was evaluated by endoglucanase, xylanase, filter paper (FPU) and β-glycosidase activities. For the application of the enzymes, a central composed response surface design with 5 repetitions of the central point was used, taking enzyme volume and hydrolysis time as factors. Such cultivation yielded the following enzymatic activities: 723 U gss-1 of endoglucanases, 2024 U gss-1 of xylanase, 12.6 U gss-1 of FPU and 41 U gss-1 of β-glucosidase. The results of the application tests indicated the best conditions as 7.0 mL of the enzyme extract (4.2 FPU) and 6 hours for BIN and BOU. The best cellulose-glucose conversions were obtained for BOU, reaching 32.1 % at 65 ºC. In conclusion, the enzyme production in the packed bed bioreactor was efficient and BOU pretreatment improved the hydrolysis of biomass, increasing the efficiency of conversion of cellulose to glucose.